Ad-based social media interventions increase belief accuracy and generate pro-social opinions among non-news readers - Erin Wertz; Maria Babińska; Dominik Batorski; Debra Louison-Lavoy; Nicholas Blazer; Nancy S. Noble; Magdalena Wojcieszak (PLoS ONE, 2026)
Democratic challenges are often attributed to the spread of misleading, untrustworthy, or biased information, leading scholars to focus on minimizing exposure to such “bad” content online. Instead, we introduce a scalable intervention to put factual and verified public affairs information in users’ social media feeds to make them better informed and more resilient to various online threats. We conducted 48 field quasi-experiments using Instagram ads targeting news non-users to enhance their belief accuracy, democratic attitudes, and behavioral intentions related to climate change, COVID-19 vaccines, media literacy, and election integrity. The treatment videos reached 2,496,878 Instagram accounts, 690,470 users watched at least 50% of the video, and 40,584 of those users completed post-test assessment. The intervention was effective: 46 out of 48 of the quasi-experiments had positive effect sizes and 40 out of 48 achieved statistical significance. The intervention predicted not only belief accuracy but also attitudes, media literacy, and — to some extent — behavioral intentions related to vaccination. These patterns emerged across topics, did not dissipate with time (two of three climate change quasi-experiments show continued effects), and were not contingent on persuasive appeals and format features presented in the ads.